Reduction of Colorado potato beetle damage by various organic mulches - Winkler, Julian; Junge, Stephan M.; Nasirahmadi, Abozar; Hensel, Oliver; Finckh, Maria R.; Kirchner, Sascha M. (Frontiers in Agronomy, 2024)
IntroductionThe Colorado potato beetle (Leptinotarsa decemlineata) (CPB) is a major threat to potato crops in Europe, Asia, and America. In Europe, it is expected that climate change will cause the species to expand its range northwards and allow for an additional generation per year in regions where it is already established. The effectiveness of insecticides, a common method of control, is decreasing due to the emergence of resistance to several substances. Therefore, research into alternative measures is becoming increasingly necessary. One preventive measure that has already been shown to have great effects in past studies is the use of organic mulch. For organic mulching, conserved or freshly cut plant material is spread on the field usually when the potato emerges. Previous research has mainly used cereal straw for this purpose in plots that are relatively small compared to actual agricultural fields. Materials and methodsTo address the lack of large-scale field trials in the literature, a series of on-station and on-farm field trials were conducted in this study. Organic, legume-rich mulches were used primarily, which so far have not been extensively investigated. Over a period of four years and in a total of six field trials, CPB and larval infestations were assessed. Results and discussionOur results show effects on the initial infestation of young plants by adult CPB and on the emergence time of the first two larval stages. By the time of flowering, when the feeding effect of CPB on yield is known to be greatest, L3 and L4 larvae were reduced by about 30% in the on-station trials and by about 40% in the on-farm trials. In addition, when CPB larval stages were used to calculate a weighted daily leaf consumption per stage, total calculated leaf consumption was on average about 40% lower in the mulch treatments across all sampling dates and all trials. The recorded yields were equal or higher in the mulched treatments. In conclusion, organic mulching can effectively reduce CPB damage even on a large scale and can have a positive impact on yield. Further agronomic benefits of mulching, as well as drawbacks and putative mechanisms of action, are discussed.